MENTAL LEXICON PRODUCED BY THE FIFTH SEMESTER STUDENTS OF STIKES BINA SEHAT PPNI MOJOKERTO (A CASE STUDY OF WORD ASSOCIATION TEST) - WIDAYANTI, DIAH (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Psycholinguistics, Mental Lexicon, Word Association Test, Stikes Bina Sehat PPNI Mojokerto. Psycholinguistics has three areas, they are language production, language comprehension and language disorder. This research investigates more in language production using word association test. Word association test is a test to give response on a stimulus word. This research intends to investigate word association produced by the medical students. The researcher uses Peppard’s theory (2007) to classify word association type. There are two aims in this research. The first is to find out the types of word association produced by the fifth semester students of Stikes Bina Sehat PPNI Mojokerto and the second is to find out to what extent their medical knowledge influences the participants in choosing the responses.This research uses qualitative approach. The researcher uses word association test to collect the data. There are 8 stimulus words which trigger 448 responses from 56 participants. In analyzing the data, the researcher uses two steps. Firstly, the researcher classifies the data into three types of word association based on Peppard’s theory. Secondly, the researcher analyses the data and gives explanation about each of the classification.This research indicates syntagmatic response as the highest response which consists of 198 responses in encyclopedic knowledge, 106 responses in collocation and 58 responses in multi word item. The second type is found in paradigmatic response which consists of 4 hyponymy, 45 hypernymy, 31 synonymy and 6 coordination. Phonological and orthographical response are not found in this research. In some stimulus words, the participants produce responses that has relationship with medical knowledge. It proves that the participants are influenced by their medical knowledge and experience in choosing responses.The researcher suggests Study Program of English to provide more references about psycholinguistics to enrich the related literature. Besides, the researcher also suggests for the next researchers, to apply word association test in other groups of participants or investigate more about how female and male produce response word in word association test.